2020
DOI: 10.1371/journal.pone.0240913
|View full text |Cite
|
Sign up to set email alerts
|

Factors impeding the supply of over-the-counter medications according to evidence-based practice: A mixed-methods study

Abstract: Objective Despite the positive attitudes pharmacists have toward evidence-based practices (EBPs), its application in community pharmacies in Saudi Arabia is lacking. Therefore, this study aimed to explore and assess EBPs by community pharmacists in Saudi Arabia when they dispense over-the-counter (OTC) medications for three minor ailments: diarrhea, cough, and the common cold. Research design and methods We used a mixed-methods approach consisting of two study parts. The first was a quantitative investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…A broad variety of terms were used in the studies to the individuals used to perform the simulated visits. The individuals were described as SP 37 (82.2%), 19 , 20 , 22 - 28 , 30 - 36 , 38 , 41 - 45 , 47 - 52 , 54 - 56 , 58 - 63 simulated client 10 (22.2%), 18 , 21 , 24 , 27 , 29 , 35 , 39 , 40 , 47 , 57 and mystery shopper 10 (22.2%), 23 , 26 , 29 , 32 , 40 - 42 , 54 , 55 , 59 mystery patient 3 (6.7%), 21 , 26 , 32 pseudo patient 4 (8.9%), 21 , 23 , 24 , 55 pseudo customer 3 (6.7%), 23 , 24 , 42 investigator 2 (4.4%), 18 , 47 covert patient 1 (2.2%), 21 pseudo patron 1(2.2%), 23 standardized client 1(2.2%), 21 standardized patient 1 (2.2%), 55 shopper patient 1(2.2%), 23 simulated customer 1 (2.2%), 39 simulated shopper 1 (2.2%), 21 secret shopper 1 (2.2%), 58 surrogate shopper 1 (2.2%), 21 surrogate client 1 (2.2%). 21 In addition, many articles provided brief background or defined what was meant by SP or the equivalent term 17 (37.8%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A broad variety of terms were used in the studies to the individuals used to perform the simulated visits. The individuals were described as SP 37 (82.2%), 19 , 20 , 22 - 28 , 30 - 36 , 38 , 41 - 45 , 47 - 52 , 54 - 56 , 58 - 63 simulated client 10 (22.2%), 18 , 21 , 24 , 27 , 29 , 35 , 39 , 40 , 47 , 57 and mystery shopper 10 (22.2%), 23 , 26 , 29 , 32 , 40 - 42 , 54 , 55 , 59 mystery patient 3 (6.7%), 21 , 26 , 32 pseudo patient 4 (8.9%), 21 , 23 , 24 , 55 pseudo customer 3 (6.7%), 23 , 24 , 42 investigator 2 (4.4%), 18 , 47 covert patient 1 (2.2%), 21 pseudo patron 1(2.2%), 23 standardized client 1(2.2%), 21 standardized patient 1 (2.2%), 55 shopper patient 1(2.2%), 23 simulated customer 1 (2.2%), 39 simulated shopper 1 (2.2%), 21 secret shopper 1 (2.2%), 58 surrogate shopper 1 (2.2%), 21 surrogate client 1 (2.2%). 21 In addition, many articles provided brief background or defined what was meant by SP or the equivalent term 17 (37.8%).…”
Section: Resultsmentioning
confidence: 99%
“…A broad variety of terms were used in the studies to the individuals used to perform the simulated visits. The individuals were described as SP 37 (82.2%), 19,20,[22][23][24][25][26][27][28][30][31][32][33][34][35][36]38,[41][42][43][44][45][47][48][49][50][51][52][54][55][56][58][59][60][61][62][63] simulated client 10 (22.2%), 18,21,24,27,29,35,39,40,47,5 7 and mystery shopper 10 (22.2%), 23,26,29,32,[40][41][42]54,55,59 mystery patient 3 (6.7%), 21,26,…”
Section: The Characteristics Of the Simulated Patient And Simulated V...mentioning
confidence: 99%
“…Furthermore, more than 40% of parents relied on information received from community pharmacists about the appropriate dosage of the OTC medication. However, low adherence to evidence-based practices by community pharmacists in Saudi Arabia when dispensing OTC medication has been reported, as only 40% of pharmacists dispensed OTC medications according to the recommended guidelines [31,32]. Those results highlight the importance of monitoring community pharmacists and encouraging them to keep updated while taking the initiative to actively guide patients and provide information about the proper use of OTC medications and their possible negative outcomes when dispensing medications [33].…”
Section: Discussionmentioning
confidence: 99%
“…Very little attention has been paid to community pharmacists' information needs for evidence-based self-medication counselling. Up to now, research has tended to focus more on investigating barriers, educational interventions and the status quo of counselling-practice [9,12,13,19,20,41]. This study was therefore set out with the aim of gaining an insight into their information needs to help facilitate EbPharm into practice.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published studies have shown, however, that external evidence in particular is only sparsely integrated into everyday counselling [9][10][11][12][13][14][15][16][17][18]. Barriers such as a lack of time, and missing information resources were identi ed as the main reason causing the evidence-to-practice-gap [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%